Selective inhibition of human AKR1B10 by n-humulone, adhumulone and cohumulone isolated from Humulus lupulus extract - Jan Moritz Seliger and Serhat Sezai Cicek and Lydia T. Witt and Hans Jörg Martin and Edmund Maser and Jan Hintzpeter (Molecules, 2018)
Hop-derived compounds have been subjected to numerous biomedical studies investigating their impact on a wide range of pathologies. Isomerised bitter acids (isoadhumulone, isocohumulone and isohumulone) from hops, used in the brewing process of beer, are known to inhibit members of the aldo-keto-reductase superfamily. Aldo-keto-reductase 1B10 (AKR1B10) is upregulated in various types of cancer and has been reported to promote carcinogenesis. Inhibition of AKR1B10 appears to be an attractive means to specifically treat RAS-dependent malignancies. However, the closely related reductases AKR1A1 and AKR1B1, which fulfil important roles in the detoxification of endogenous and xenobiotic carbonyl compounds oftentimes crossreact with inhibitors designed to target AKR1B10. Accordingly, there is an ongoing search for selective AKR1B10 inhibitors that do not interact with endogeneous AKR1A1 and AKR1B1-driven detoxification systems. In this study, unisomerised α-acids (adhumulone, cohumulone and n-humulone) were separated and tested for their inhibitory potential on AKR1A1, AKR1B1 and AKR1B10. Also AKR1B10-mediated farnesal reduction was effectively inhibited by α-acid congeners with Ki-values ranging from 16.79 ± 1.33 µM (adhumulone) to 3.94 ± 0.33 µM (n-humulone). Overall, α-acids showed a strong inhibition with selectivity (115–137 fold) for AKR1B10. The results presented herein characterise hop-derived α-acids as a promising basis for the development of novel and selective AKR1B10-inhibitors.
Keywords: Aldo-keto reductases; Alpha-acids; Cancer; Farnesal reduction; Hops; Humulone; Humulus lupulus; Selective inhibition; Tight-binding inhibition